The European Central Bank: the time is ripe for a major revision of its strategy - Peter Bofinger (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
A revision of the European Central Bank's (ECB) strategy is urgently needed. For the new strategy, it is important to define the inflation target explicitly in symmetrical terms. Environmental policy objectives can in principle be reconciled with the ECB's mandate as long as they do not conflict with the objective of monetary stability. An essential element of any strategy is a heuristic that makes it relatively easy for the public to monitor whether monetary policy decisions are in line with the mandate. Among the possible heuristics, monetary targeting and the Taylor rule have to be ruled out while 'inflation targeting' offers a relatively simple navigation system for monetary policy discussions.
Keywords: E42; E52; E58; 330; monetary policy; European Central Bank; monetary policy strategies; inflation targeting